Influence of different grazing intensity on above-ground biomass in Mongolian rangeland (Proceedings of the Mongolian Academy of Sciences, 2019)
In the last two decades, the quality of Mongolian rangeland has degraded primarily owing to overgrazing and climate change. This has government challenged to improve land usage and gather information about the tolerance of the rangeland. The aim of this research was to examine the effect of cutting frequency (four, three, two and one), cutting height (0 and 3 cm) and duration of cutting on above-ground biomass at different degradation levels of Fescue-forbs rangeland. Three sites were selected with different degradation levels; slightly, moderately and heavily degraded. The cutting experiment was randomized with complete block design with five replications. Samplings were carried out in 2006, 2007 and 2008. In 2009, all the plots of rangelands were cut at the same time in August and at 0 cm height and the results were analyzed. The results showed that total biomass was influenced by cutting frequency, cutting height and the duration of cutting. Biomass decreased considerably with increasing cutting frequency in most cases when cutting height was 0 cm but small changes were noticed when cutting height was 3 cm. The biomass decreased by 30-54% when cut four times a year at 0 cm in slightly- and moderately-degraded sites. Year of duration influenced biomass significantly at slightly- and heavily degraded sites.